Visual recovery in orbital vasculitis. Issue 10 (October 1988) - Bagegni, A; Lyness, R W; Johnston, P B; Douglas, J F
Abstract : A 46-year-old woman with polyarteritis nodosa and chronic renal failure developed sudden loss of vision which was associated with orbital vasculitis. Treatment with cyclophosphamide produced rapid improvement in vision, which has been preserved with maintenance doses of cyclophosphamide and prednisolone.